Beyond Lancaster and York: Contextualizing Wars of the Roses Board Games in Scholarly Consensus - Dowell, Nathan J. (My University, 2020)
The English Wars of the Roses, fought from roughly 1455 to 1485 between the royal houses of Lancaster and York, have proven surprisingly popular among board game designers. In creating games that seek to demonstrate the infamous chaos of the wars, these games have also begun engaging with each other on a historical level—each new game attempts to build upon the achievements of the first by drawing closer and closer to the current scholarly consensus. Despite this unique feat of forming an academic debate through the medium of board games, however, no designer has yet fully reflected key elements of the scholarly consensus. For this reason, this paper lays out an original design, intended as a contribution to the ongoing discussion of how the wars should best be adapted into tabletop games. This paper describes the ways in which this new design constitutes an important addition to the set of Wars of the Roses board games, through incorporating both newer innovations in game design and recent scholarship. First, the template for this type of board game is traced back to the Avalon Hill title Kingmaker. It is then explained how additional games have diverged from Kingmaker’s model, but have not yet fully matched the current academic consensus regarding the motivations and timeframe of the war. Finally, the original design is explained, highlighting the ways in which this new game selectively breaks from Kingmaker’s precedent in order to better reflect these elements that scholars find key to explaining the wars.